Pete the cat : rocking in my school shoes - Litwin, Eric.; Dean, James, 1957- (New York : HarperCollins, 2011)
Pete the cat wears his school shoes when visiting the library, the lunchroom, the playground, and more while singing his special song.
Keywords: Stories in rhyme; Schools -- Fiction; Cats -- Fiction; Shoes -- Fiction; Singing -- Fiction